Difference Between Social Capital Caregivers of Schizophrenic Patients Who Have the Highest and Lowest Burden - Yeni Maya Sari; Aris Sudiyanto; Adriesthi Herdaetha (Bulletin of Counseling and Psychotherapy, 2023)
Mental disorders cause economic, social, physical, and even psychological burdens on the sufferer and the family. The role of the family as an informal nurse (caregiver) greatly influences the patient’s healing. Long treatment and inhumanity of schizophrenic patients is a heavy burden and cause stress on the caregiver, so proper social capital is needed. This study aims to determine the difference between social capital in caregivers of schizophrenic patients with the highest load and caregivers of schizophrenic patients with the lowest gear at RSJD Surakarta. This study is a retrospective study with a case-control approach, conducted on 100 caregivers of schizophrenic patients where 25 caregivers with the highest caregiver load as cases and 25 caregivers with the lowest social load as a control, using social capital questionnaire instruments and validated caregiver load questionnaires. Based on the study's data, normal and homogeneous social capital data distribution was obtained in cases and controls. For the normality test results, the sig level value was obtained > 0.05, namely 0.084 and 0.200, and the homogeneity test obtained a sig level value of > 0.05, namely 0.066. From the results of the T-test, a Sig (2-tailed) value of < 0.005 was obtained, which is 0.000. There is a significant difference between social capital in caregivers of schizophrenic patients with the highest burden (cases) and in caregivers of schizophrenic patients with the lowest load (control).